Нативний додаток на основі багатовимірного нео-фаззі нейрону - Мірошниченко, Н. С.; Перова, І. Г. (ХНУРЕ, 2019)
Having received a series of medical data that was pre-treated, the multidimensional neo-phase neuronal training was conducted on these data. The percentage of errors in training and testing of this system is obtained. For visibility of the results, a web application was created
Keywords: нео-фаззі нейрон; сплайн; навчання; ol-line діагностування